(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The phrase “Clinical legal education” is significant in making law students ready enough to practice the law in efficacious manner. It includes providing leanings to students to become advocate by way of “learning by doing or experience”. It is a kind education that is in the midst of phase of development and growth and in these relevant clinicians over globe are prompted to look upon the remarkable achievements and success over last 40 years that will be crucial for its future. Usually, law institutions in India provide the facility of “legal aid cells” wherein the students are involved in performing legal services for poor people. Clinics are crucial as they nurture students to practice law through making them learn significant skills like legal writing and research, interviewing, investigation and fact-finding. Moreover, students build an aspect of empathy in their work and social justice.